Interrogating questions of national belonging, difference and xenophobia in South Africa. Issue 2 (2nd April 2016) - Batisai, Kezia
Abstract: Questions about gender and sexuality that were central to the colonial project where women negotiated their connection to the nation through liaisons with men continue to be central to the process of building postcolonial African states. The establishment of many of these states has been embedded in dense body politics that often exclude genders and sexualities categorised as counter to citizenship. Exclusion in post-apartheid South Africa (SA), for instance, is evident in how black lesbians and queers are attacked and excluded for being sexually different. Consequently, one's gender, sexual and racial identities serve as a source of violence and constant negotiation for belonging to this democracy, irrespective of the progressive Constitution. The feeling of not being a 'proper' citizen is equally evident in how nationals from the northern part of SA are in some spaces constructed by fellow citizens as bodies that do not belong. These polarised constructions generate outsider identities that are informed by notions of 'inferior pigmentation and language' vis-à-vis 'dominant ones'. Such dichotomised images of citizenship are reinforced by ever-evolving grammars and vocabularies about people foreign to SA, whose bodies and privacy warrant intrusion in very violent nationalised, racialised, gendered and sexualised ways, as evidenced by the 2008 and 2015 xenophobic attacks. Informed by my intersecting positionalities as a black foreign national who has lived in SA since 2008, the article analyses Zimbabwean migrants' experiences of constantly negotiating the politics of national belonging and difference in SA that emerged during fieldwork engagements in Johannesburg between 2008 and 2015. The article interrogates subtle and overt institutionalised and everyday technologies of difference that not only force foreign nationals to live through heavily patrolled black bodies marked as different within specific temporal landscapes, places and spaces, but are also core to the xenophobic grammar that frames Zimbabweans as bodies that destabilise the very foundation and survival of the nation.